The Impact of Investment Knowledge, Investment Returns, and Investment Risk on Investors' Investment Interests - Murwaniputri, Hesti; Bleskadit, Novalia Herlina (Universitas Syiah Kuala, 2023)
This study aimed to assess the influence of investment knowledge, investment returns, and investment risk on investors' interest in Jayapura City. Utilizing purposive sampling, a sample of 100 individuals participated in this quantitative research. The findings, obtained through t-tests, demonstrate that investment knowledge and investment returns exert a significant and positive impact on investors' interest in Jayapura City. However, investment risk was found to have an insignificant and negative effect on their investment interest in the same city. Further analysis employing an F-test revealed that investment knowledge, investment returns, and investment risk collectively possess a significant influence on investors' investment interest in Jayapura City. These outcomes suggest that investors in Jayapura City are more inclined to invest when they possess better investment knowledge and anticipate higher returns. Conversely, while investment risk plays a role, its effect was not statistically significant in this context. These insights can guide investment strategies and education initiatives in the region, potentially encouraging more informed investment decisions and fostering a favorable investment climate in Jayapura City.